Repelling property of the methalonic and hexanic extracts of Sambucus ebulus L. against the Culex pipiens: in-vitro study - H Fathi (مجله دانشگاه علوم پزشکی گرگان, 2017)
Background and Objective: The anti inflammatory, analgesic, antioxidant of Sambucus ebulus L. have been reported in several studies. This study was done to assess the repelling property of the methalonic and hexanic extracts of Sambucus ebulus L. against the Culex pipiens.